Heterogeneity and confinement of HIV prevalence among pregnant women calls for decentralized HIV interventions: Analysis of data from three rounds of HIV sentinel surveillance in Karnataka: 2013-2017 - Santhakumar Aridoss; Malathi Mathiyazhakan; Nagaraj Jaganathasamy; Ganesh Balsubramanian; Manikandan Natesan; V M Padmapriya; Joseph K David; Pradeep Kumar; Elangovan Arumugam (Wolters Kluwer Medknow Publications, 2021)
Background: The HIV sentinel surveillance (HSS) serves to estimate the levels and trend of HIV prevalence among high-risk, bridge, and general population and monitors HIV management at national, state, and district levels. Data from HSS are valuable in understanding the risk factors associated with HIV transmission with particular demographic characteristics. Objectives: The objective was to analyze the sociodemographic profile of the pregnant mothers attending the antenatal care (ANC) clinics in Karnataka, in order to understand the dynamics of HIV within the general population in Karnataka. Materials and Methods: Study design: this was a cross-sectional study conducted using consecutive sampling method. Study setting: the surveillance was conducted at select antenatal clinics, in Karnataka, India, between January and March, in the years 2013, 2015, and 2017. Methodology: in total, 74,278 eligible pregnant women aged between 15 and 49 years, attending the sentinel sites for the first time during the surveillance period, were included in the study. Information on their sociodemographic characteristics and blood samples was collected. Results: HIV prevalence among the ANC clinic attendees has significantly declined, reaching a recent stabilization. The risk factors significantly associated with HIV among pregnant women were age, education, occupation, and marital status. HIV is highly concentrated in the northern and southern districts of Karnataka. Conclusion: Despite the declining trends of HIV prevalence in Karnataka, the epidemic is heterogeneous and concentrated within the state, calling for decentralized region-specific interventions.